Development and Initial Validation of the Coping With Academic Demands Scale: How Students in Accelerated High School Curricula Cope With School-Related Stressors. (July 2015) - Suldo, Shannon M.; Dedrick, Robert F.; Shaunessy-Dedrick, Elizabeth; Fefer, Sarah A.; Ferron, John
Successful coping with academic demands is important given the inverse relationship between stress and positive adjustment in adolescents. The Coping With Academic Demands Scale (CADS) is a new measure of coping appropriate for students pursuing advanced high school curricula, specifically Advanced Placement (AP) classes and the International Baccalaureate (IB) program. We developed the CADS in parallel with a new measure of stress designed for this same population. We generated an initial item pool using multiple sources including focus groups and individual interviews with 177 students, 72 teachers, and 47 parents. Multiple iterations of expert review and item analyses resulted in 120 items, which were completed by 727 high school students in six schools (312 IB, 415 not in IB but taking at least one AP class). Exploratory factor analyses and additional item review indicated a 16-factor solution with 58 items. Cronbach's alpha reliabilities for the factors ranged from .53 to .90, with 11 factors exceeding .70. All 16 factors had test–retest reliabilities greater than .70. Support for the construct validity of the CADS scores was provided using a nomological network, which specified relationships between the CADS and broader dimensions of school-related coping dimensions (task, avoidance, and emotion-oriented), as well as indicators of achievement (grade point averages) and mental health (life satisfaction). An additional seven items that were not part of the 16-factor CADS, but which were identified as relevant in different phases of instrument development, are provided as a resource for researchers.